PRINCIPAL LEADERSHIP IN DEVELOPING AL-QUR'AN LEARNING MANAGEMENT - Salim Salim; Enung Hasanah (JURNAL AL-TANZIM, 2021)
This study aims to determine the implementation of the Principal's leadership in developing Al-Qur'an learning management that has been implemented in SMP Negeri 8 Yogyakarta City. The output of learning the Qur'an which makes the majority of students of SMP Negeri 8 Yogyakarta City able to read the Qur'an well, even some students are able to memorize the Qur'an up to 2 juz is something that is interesting to study. This research uses a qualitative approach. Participants in this study were the Principal, Islamic religious teachers and teachers of the Qur'an. The techniques used in data collection were done by using interviews, observation and documentation. Data analysis was carried out in two stages; (1) research in the field, the analysis results in this first stage are in the form of temporary conclusions obtained from the results of observations and document studies using the inductive analysis model. The conclusion data obtained in the first stage of analysis is then developed in the second stage of analysis, namely analysis after data collection. At this stage, all data were analyzed inductively by using descriptive qualitative research. The conclusion of this study shows that the Principal can develop the management of learning the Qur'an well.